Adinkra: imagens da ancestralidade africana na cultura brasileira - Silva, Marisa Francisca da (2023)
The presence of the adinkra, images of the Akan culture of Ghana and Ivory Coast, are increasingly recurrent in Brazilian culture today, which instigates questions about this phenomenon and its impacts. The research is dedicated to this investigation, also considering the communicational mediation around the adinkra. The methodology aims to return to the past, understand the present, and project future scenarios. It begins with traditional Akan culture and the traditional objects that the adinkra carry, observing the communication of these images in modern-day Brazil in other media relations and the capacity that some images have to affect us. To this end, the theoretical framework includes Harry Pross with Media Theory, and Norval Baitello, who addresses the environmentality of primary, secondary and tertiary media, and their impacts. It also includes Aby Warburg, who, by identifying the migration of images from one time and place to another, noted their ability to provoke passions. The research verifies the link in a network of communicational interactions around the adinkra in Brazilian culture, and its possible impacts, including the construction of future scenarios